Information Systems Research Relevant Theory and Informed Practice - Kaplan, Bonnie; Truex, Duane P.; Wastell, David; Wood-Harper, A.Trevor (IFIP Advances in Information and Communication Technology, 2004)
Information Systems Research: Relevant Theory and Informed Practice comprises the edited proceedings of the WG8.2 conference, "Relevant Theory and Informed Practice: Looking Forward from a 20-Year Perspective on IS Research," which was sponsored by IFIP and held in Manchester, England, in July 2004. The conference attracted a record number of high-quality manuscripts, all of which were subjected to a rigorous reviewing process in which four to eight track chairs, associate editors, and reviewers thoughtfully scrutinized papers by the highly regarded as well as the newcomers. No person or idea was considered sacrosanct and no paper made it through this process unscathed. All authors were asked to revise the accepted papers, some more than once; thus, good papers got better. With only 29 percent of the papers accepted, these proceedings are significantly more selective than is typical of many conference proceedings. This volume is organized in 7 sections, with 33 full research papers providing panoramic views and reflections on the Information Systems (IS) discipline followed by papers featuring critical interpretive studies, action research, theoretical perspectives on IS research, and the methods and politics of IS development. Also included are 6 panel descriptions and a new category of "bright idea" position papers, 11 in all, wherein main points are summarized in a pithy and provocative fashion